Combined effect of boost pressure and injection timing on the performance and combustion of CNG in a DI spark ignition engine - Aziz, A. Rashid A. (2017)
There is an increasing interest in supercharging spark ignition engines operating on CNG (compressed natural gas) mainly due to its superior knock resisting properties. However, there is a penalty in volumetric efficiency when directly injecting the gaseous fuel at early and partial injection timings.